Pariahs of Latin America: The MST and 500 years of Indigenous, Black and Popular Resistance - Rubbo, Deni Irineu Alfaro (Pontifícia Universidade Católica de São Paulo, 2015)
Based on criticisms of the notions of “progress” and “civilization” advanced by José CarlosMariátegui, as well as on a desire to celebrate the pariahs of Latin America, this article describesand analyzes the participation of the MST in the Continental Campaign of 500 Years ofIndigenous, Black and Popular Resistance, part of the MST’s internationalist political history.Based principally on interviews and historical documents, the article portrays the constructionof innumerable meetings, debates and texts by peasant, indigenous and black movements of the subcontinent. The social experience of the campaign creates a decisive political identitybetween the MST and subaltern sectors in Latin America, which attempt to demonstrate “thecatastrophic side of modernity.”